The Future Development of Hong Kong Dollar Exchange Rate Regime - Yi, Xinwen (International Journal of Global Economics and Management, 2024)
In the context of the developing economies, this paper examines the future outlook of Hong Kong's Linked Exchange Rate System. There is an emerging need for a re-evaluation of the system after a 40-year stable period of operation. This paper adopts a qualitative analysis to evaluate the current merits and dilemmas of the Hong Kong Dollar and its link with the Renminbi. It examines the possibility of pegging the Hong Kong Dollar to the Renminbi and the pre-conditions to be met for implementation. As well as the implications of such reform for both Hong Kong and the Mainland.